Quizizz Website as an Online Assessment for English Teaching and Learning: Students’ Perspectives - Dinda Firly Amalia (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2020)
This paper aimed to investigate the students’ perspectives toward the use of Quizizz as an online assessment tool for English teaching and learning, especially on a formative one. The research design of this study was descriptive qualitative. The subjects of the study were 20 students of Dynamic English Course. The data was collected by asking the students to fill the questionnaire. The data analysis was implementing the Likert Scale. The result of the study showed positive perspectives of the students toward the use of Quizizz. In conclusion, the students strongly agreed that Quizizz has an attractive display which is interesting and fun, students can’t cheat during the test, Quizizz creates a competitive atmosphere in the classroom, and Quizizz is better than the offline traditional test.